Cognitive styles of consumer initiators - Foxall, Gordon R.
Foxall's study of the Kirton Adaptor-Innovator theory following work in three organizations concerned with food brands and products and two with the use of computer software suggests a more complex psychographic composition of consumer innovator segments than has generally been appreciated.
Accounts of consumer innovativeness show two trends : theoretical sophistication in which innovative behaviour is attributed to abstract personality constructs such as innate and inherent innovativeness, and a resounding lack of empirical evidence that innovative behaviour is more than weakly related to traits of personality. The difficulty is compounded by terminological confusion. This article proposes that Kirton's theory of adaptive-innovative cognitive style suggests solutions to both the terminology issue and the problem of equivocal empirical findings. It describes five studies of innovative consumer behaviour, three relating to the purchase of new food brands and products, and two to the use of computer software. The findings indicate a more complex psychographic composition of consumer innovator segments than is generally appreciated in the marketing and new product development literatures.
Keywords: Consumer initiators